Nigeria Upstream Petroleum Sector and Revenue Generation: The Moderating Role of Accounting Artificial Intelligence System - Eshemokhai Balogun; Yila Ayuba (International Journal of Management, Accounting and Economics)
This paper has conceptually reviewed the Nigerian upstream petroleum sector and revenue generation with accounting artificial intelligence system as a moderating variable. An in-depth exploration of existing literature was made to buttress the views expressed by the researchers and prior research with regard to the subject matter examined. The study employs the desk-top review methodology by examining existing literature on the topic in order to get adequate firsthand information. Findings emanating from the conceptual review indicate that oil and gas serve as a major source of revenue for the Nigerian government, and as such, there should be adequate accountability for the number of barrels extracted from the upstream exploration. Based on this, the study suggested that the Nigerian government, policymakers, and upstream petroleum sector regulators should engage key players operating in the artificial intelligence and machine learning language industries to design and develop an accounting artificial intelligence solution system that will assist the upstream corporation in realising the actual volume of crude oil extracted and determining the actual revenue that is accrued to the revenue collection agencies without human disruption and manipulation on behalf of the Nigerian government.